Variability in the effects of bilingualism on task switching of cognitively healthy and cognitively impaired older bilinguals - Chen, Hui-Ching; Yow, W. Quin (Frontiers in Language Sciences, 2023)
The impact of bilingualism on executive function has been extensively discussed, but inconsistent evidence has been reported. These discrepancies may stem from the complexities of being bilingual and the various ways of measuring bilingual experiences. This study aims to clarify the debate by providing a systematic critique and analysis on how different measurements of bilingualism can lead to different results within the same group of bilinguals. We tested 48 cognitively healthy (CH) and 43 cognitively impaired (CI) older adults (Mage = 73.25 and 79.72 years, respectively) using the color-shape switching task. We assessed bilingualism using six different methods based on dominant language usage: five categorical computations and one continuous measurement. The results varied depending on the method of measuring bilingualism and the participant group. For CH older adults, a significant effect of bilingualism on cognition performance was observed only when using the categorical variable based on a cutoff of 70% dominant language usage, but not with other categorical computations or the continuous approach. For CI older adults, no effect of bilingualism was found, regardless of the type of measurement used. In summary, our results demonstrated that different measurements of language use can yield different results within the same group of bilinguals using a single task. Our study yielded important implications for bilingual research: the findings challenge the current methodologies used to describe bilingual experiences and call for care and consideration of context and the complexity when examining the effects of bilingual experience on executive functions.